'A Fiction to Mock the Cuckold': Reinvigorating the Cliché Figure of the Cuckold in Abdulrazak Gurnah's By the Sea (2001) and Gravel Heart (2017). Issue 3 (3rd July 2021) - Bosman, Sean James
ABSTRACT: This article argues that Abdulrazak Gurnah reinvigorates the cliché figure of the cuckold into a complex narrative device. His cuckolds serve as nexuses through which he expresses some of his authorial concerns in By the Sea (2001) and Gravel Heart (2017). While Rajab Shaaban Mahmud and Masud Yahya are considered traditional cuckolds by other characters in their respective novels, Gurnah's complex use of multiple narrative situations exposes the superficiality of this identity to his readers. In so doing, Gurnah configures cuckolds as ambiguous figures to expose the power dynamics amongst multiple masculinities and the dangers of casting others as hapless victims. This article delineates similarities between the figure of the cuckold as it is traditionally portrayed and Gurnah's cuckold characters, before it describes how the author has repurposed the trope. It draws on theories of identity by Stuart Hall and descriptions of hegemonic masculinities proposed by R.W. Connell. It also uses the notion of the comforts of victimhood developed in separate works by Taro Iwata and Viet Thanh Nguyen. These theories inform the close readings of the primary texts presented throughout the article. Ultimately, the argument asserts that Gurnah refreshes a stagnant literary trope by imbuing the cuckold with agency.